Diagnostic Performance and Safety of Positron Emission Tomography with 18F-rhPSMA-7.3 in Patients with Newly Diagnosed Unfavourable Intermediate- to Very-high-risk Prostate Cancer: Results from a Phase 3, Prospective, Multicentre Study (LIGHTHOUSE) - Surasi Devaki S.; Eiber Matthias; Maurer Tobias; Preston Mark A.; Helfand Brian T.; Josephson David; Tewari Ashutosh K.; Somford Diederik M.; Rais-Bahrami Soroush; Koontz Bridget F.; Boström Peter J.; Chau Albert; et al. (Elsevier B.V., 2025)
Background: Radiohybrid (rh) 18F-rhPSMA-7.3 is a novel high-affinity prostate-specific membrane antigen (PSMA)-targeting radiopharmaceutical for prostate cancer (PCa) imaging.
Objective: To evaluate the diagnostic performance and safety of 18F-rhPSMA-7.3 in newly diagnosed PCa patients planned for prostatectomy.
Design, setting, and participants: Data on 18F-rhPSMA-7.3 were reported from the phase 3 prospective, multicentre LIGHTHOUSE study (NCT04186819).
Outcome measurements and statistical analysis: Patients underwent positron emission tomography/computed tomography (PET/CT) 50–70 min after an injection of 296 MBq 18F-rhPSMA-7.3. Images were interpreted locally and by three blinded independent readers. The coprimary endpoints were patient-level sensitivity and specificity for the detection of pelvic lymph node (PLN) metastases, validated using histopathology at PLN dissection. Prespecified statistical thresholds (lower bounds of 95% confidence interval [CI]) were set at 22.5% for sensitivity and 82.5% for specificity.
Results and limitations: Of 372 patients screened, 352 had evaluable 18F-rhPSMA-7.3-PET/CT and 296 (99 [33%] with unfavourable intermediate-risk [UIR] and 197 [67%] with high-/ very-high-risk [VHR] PCa) subsequently underwent surgery. As per the independent reads, 23–37 (7.8–13%) patients had 18F-rhPSMA-7.3–positive PLN. Seventy (24%) patients had one or more positive PLNs on histopathology. The sensitivity for PLN detection was 30% (95% CI, 19.6–42.1%) for reader 1, 27% (95% CI, 17.2–39.1%) for reader 2, and 23% (95% CI, 13.7–34.4%) for reader 3, not meeting the prespecified threshold. Specificity was 93% (95% CI, 88.8–95.9%), 94% (95% CI, 89.8–96.6%), and 97% (95% CI, 93.7–98.7%), respectively, exceeding the threshold for all readers. Specificity was high (92%) across both risk stratifications. Sensitivity was higher among high-risk/VHR (24–33%) than among UIR (16–21%) patients. Extrapelvic (M1) lesions were reported for 56–98/352 (16–28%) patients who underwent 18F-rhPSMA-7.3-PET/CT irrespective of surgery. Verification of these (predominantly by conventional imaging) gave a verified detection rate of 9.9–14% (positive predictive value, 51–63%). No serious adverse events were observed.
Conclusions: Across all risk stratifications, 18F-rhPSMA-7.3-PET/CT had high specificity, meeting the specificity endpoint. The sensitivity endpoint was not met, although higher sensitivity was noted among high-risk/VHR than among UIR patients. Overall, 18F-rhPSMA-7.3-PET/CT was well tolerated, and identified N1 and M1 disease prior to surgery in newly diagnosed PCa patients.
Patient summary: In order to select the most appropriate treatment for patients with prostate cancer, it is critical to diagnose the disease burden accurately at initial diagnosis. In this study, we investigated a new diagnostic imaging agent in a large population of men with primary prostate cancer. We found it to have an excellent safety profile and to provide clinically useful information regarding the presence of disease beyond the prostate.